The effect of garlic extract (Allium sativum L.) (Amaryllidaceae) to eradicate the Porphyromonas endodontalis biofilm: An in-vitro research - Adi Dharma Widjaya; Meiny Faudah Amin; Aryadi; Boedi Oetomo Roeslan (Wolters Kluwer Medknow Publications, 2021)
Background: The Gram-negative bacterium Porphyromonas endodontalis is one of the causes of endodontic infections. Irrigation in root canal treatment was intended to eliminate bacteria. The garlic extract (Alium sativum Linnaeus) (Amaryllidaceae) is a natural material believed to have antimicrobial effects and may be used as an alternative irrigation solution. Objectives: The aim of this article is to evaluate the effect of garlic extract on the eradication of P. endodontalis biofilms. Methods: The A. sativum extract with concentrations of 100%, 50%, and 25%, NaOCl 5.25%, CHX 2% as a positive control, and sterile Aquadest as a negative control were used as irrigation solutions. A random sample of six groups was tested for P. endodontalis ATCC® 35406D-5TM biofilm eradication by irrigation of the A. sativum extract. Results: It was shown with a one-way analysis of variance that there was a significant difference in optical density (OD) between the results of biofilm eradication using A. sativum with concentrations of 100%, 50%, and 25% and NaOCl 5.25%, CHX 2%, and Aquadest (P < 0.05). With Tukey's post hoc test, it was shown that the OD value from the eradication of A. sativum with concentrations of 100%, 50%, and 25% did not differ significantly compared with NaOCl 5.25% or CHX 2% (P > 0.05). Conclusion: The garlic extract (A. sativum) is effective in eradicating the biofilm of P. endodontalis in vitro.